The Syntax and Semantics of a Determiner System : a case study of Mauritian creole. (Creole language library, 2011)
Within the framework of Chomsky's Minimalism and Formal Semantics, this work documents the development of the Mauritian Creole (MC) determiner system from the mid 18th century to the present. Guillemin proposes that the loss of the French quantificational determiners, which agglutinated to nouns, resulted in the occurrence of bare nouns in argument positions. This triggered a shift in noun denotation, from predicative in French to argumental in MC, and accounts for the very different determiner systems of the creole and its lexifier. MC nouns are lexically stored as Kind denoting terms, that share some of the distributional properties of English bare plurals. New MC determiners are analyzed as 'type shifting operators' that shift Kinds into predicates, and serve to establish the referential properties of noun phrases. The analysis provides evidence for the universality of semantic features like Definiteness and Specificity, and the mapping of their form and function.